Pt catalyst supported on Al2O3 modified with CeO2 and ZrO2 for Aqueous-Phase-Reforming of glycerol - Barbelli, Maria Laura (2013)
The catalytic conversion of renewable sources using processes with low energy consumption is expected to reduce damage on the environment. In this sense, significant progress in reforming of alcohol from biomass has been made. The aim of the present work was to study the aqueous phase reforming (APR) of glycerol using Pt catalysts supported on SiO2, -Al2O3, and -Al2O3 modified with CeO2 and ZrO2 (Ce4Zr1). The higher activity and H2 selectivity would be related to the less particle size or higher metal dispersion of catalysts. The redox properties of the support Ce4Zr1 favor the water gas shift reaction, increasing the yield H2. The Pt/Ce4Zr1 shows deactivation by a fast sintering, however this catalyst presents the best performance; even after three reaction cycles and regeneration.